An evaluation of dental crowding and its relation to the mesiodistal crown widths in Andhra Pradesh Population - Divya Kumar Jain; Anmol Mathur; Mansoor Saify; Tanmay Sharma; Manish Jain (Advances in Human Biology, 2021)
Introduction: Crowding of the teeth is one of the most common anomalies which makes an individual seek orthodontic treatment. Dental crowding is more disturbing to the patients when located in the anterior segment of the dental arch because it often affects the quality of the patient's smile and speech, causing social embarrassment to the patient. Materials and Methods: The maxillary and mandibular casts of 100 subjects belonging to the Andhra population between 13 and 21 years of age were selected and divided into 50 subjects crowded and 50 in the noncrowded group further; we divided the crowded and non-crowded group into 25 males and 25 females in each group. Using measurement tool, individual and collective mesiodistal crown widths of canine, first and second premolar and first molar and arch perimeter of both the maxillary and mandibular jaws were measured. Results: When both the gender were considered, the mesiodistal crown widths were statistically significant for dental crowding in both mandibular jaw (P < 0.05 for mesiodistal crown width–P > 0.05 for arch perimeter) and maxillary jaw (P < 0.05 for mesiodistal crown width–P > 0.05 for arch perimeter). When we analysed the gender wise in the non-crowded group, we found there is no significant difference in dental crowding in both mandibular jaw and maxillary jaw (P > 0.05). Mean arch perimeter of the maxillary arch in crowded females (95.56) and mean arch perimeter of the maxillary arch in crowded males (98.79) have significant difference (P < 0.05). Conclusion: This study concluded that it is the cumulative mesiodistal width of the tooth, which contribute more towards crowding, while the arch perimeter contributes much less to crowding. Thus, it is better to undergo extraction orthodontic treatment then to go for arch expansion in orthodontic patients of Andhra Pradesh who are seeking the treatment for relieving crowding.